PENGARUH MODEL SNOWBALL THROWING TERHADAP LITERASI BUDAYA SISWA KELAS IV SDN JUNTIHILIR 04 - Difa Siti Ridhania; Ani Nur Aeni; Rana Gustian Nugraha (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
ABSTRACT Cultural literacy is a literacy activity to improve the ability to understand, appreciate, analyze and apply knowledge about culture. This activity can be carried out to overcome the problem of students' low love and understanding of regional culture and other regional cultures in Indonesia. For this reason, it is necessary to carry out research that provides an alternative model, namely cultural literacy through the snowball throwing learning model with the aim of finding out the effect of the snowball throwing learning model and the differences between the control class and the experimental class regarding students' cultural literacy in elementary schools. The method used in this research is experimentation with a quantitative approach. The research results show that the use of the snowball throwing model has an effect on increasing student literacy by obtaining statistical test results with an average final ability score of 74 and an average N-Gain score of 0.45. The increase in literacy skills was strengthened by the results of the N-Gain average difference test which obtained a sig value. 0.005, which means that the increase in the literacy ability of the experimental class using the snowball throwing model is significantly better than the increase in the literacy ability of the control class using the conventional model. From the research results, it can be concluded that cultural literacy using the snowball throwing model can have an influence on increasing student literacy and is different from classes that use the conventional model. Thus, the snowball throwing model is suitable to be used to improve students' literacy understanding in elementary schools. Keywords: Cultural Literacy, Snowball Throwing, Learning Model